CALL (Computer Assisted Language Learning) as a Means of Professional Development of EFL Teachers in Indonesia: a Vygotsky’s Sociocultural Perspective - Arfiyan Ridwan (Penerbit STKIP PGRI Bangkalan, 2017)
Teacher professional development in Indonesia has widely expanded in globalization, especially with the existence of technology in instruction. Computer Assisted Language Learning (CALL) resemble one of the means to promote teachers in developing their pedagogic skill in teaching. CALL from sociocultural perspective relates the issue of culture, literacy, and identity. The present study discusses how teaching practices of teachers reflect CALL approach in the eyes of sociocultural perspective, i.e. social interaction, internalization, mediation, and psychological systems. 25 English teachers from 15 schools responded intensively in answering the online questionnaire with closed-ended and open-ended questions as well as an unstructured interview about their process of classroom instruction. Focusing on the three aspects, this article seeks to find out the relations of how CALL becomes such a way to promote secondary school teachers in Indonesia to be globalized by using technology in language instruction. Three main aspects of Vygotskian thought is used to analyze how technology-enhanced learning can impact to the EFL instruction: mediation, social learning, and genetic analysis. It turns out that Indonesian EFL secondary schools teachers make use of CALL in such a various but not advanced way due to limited knowledge and skill to the updated current technology making seminars and workshops in advanced CALL are necessary to attend